Online news and public opinion: how Malaysians respond to news on a state by-election - Mohamed, Shafizan; Syed Abdullah Idid, Syed Arabi; Abdul Manan, Kamaruzzaman (Universiti Putra Malaysia, 2019)
This study articulates the agenda setting function of online news that is shared on Facebook. Many news organizations today have their own Facebook pages in which they publish news stories or links to articles. Having facebook pages allow the newspapers to reach a wider readership as well as promote reader participation through the comments section on Facebook posts. When audience members read and subsequently comment on news articles on Facebook, it becomes possible to identify the effectiveness of a newspaper’s agenda setting function by scrutinising how the readers respond to the issues covered in the newspaper. Content analysis was done on over 450 news articles from four major online newspapers during the Semenyih by-election in Malaysia. The study found that while the online newspapers and the readers do share some issue salience, the relationship is not as simple and direct. The dynamics of Facebook now enable news readers to become more than just receiver of news. Instead, they disrupt the conventional agenda setting function by becoming commenters who influence how other readers receive and contemplate news and issues.